Dry stacking of cyclone tailings - Lugão, W.G.; Almeida, M.M.; Guimarães, A.O.; Magalhães, F.S.; Mohallem, S.D.S. (Paste 2013: Proceedings of the 16th International Seminar on Paste and Thickened Tailings, 2013)
Mining companies have been facing a challenging time safely disposing of tailings. The most common disposal technique, the disposal of total tailings in conventional impoundments, requires large surface areas and has a major impact on the environment. Therefore, the adoption of alternative and more cost effective disposal techniques is being sought by mining companies all over the world. This paper demonstrates an alternative method for disposing of cycloned tailings. The method was developed at the Serra Azul Mine, owned by ArcelorMittal Mineração Serra Azul S/A, at a site with limited space to accommodate a conventional tailings dam, and where difficulties exist in obtaining environmental licenses for traditional disposal. The project designers envisioned construction of a dry stack of tailings in several levels confined in small ‘ponds.’ The ponds are built with cyclone underflow, which acts as a drainage blanket. The interior of the ponds is built with alternate layers (0.5 m thick layers) of cyclone overflow and underflow material, using trucks. The overflow is first taken to an area to lose its high moisture content and then taken to the pond. After that, the alternate disposal is carried out. To minimise erosion, the downstream face of the stack is covered with coarser tailings, obtained from jigging. The starter dike is built with rockfill to increase the overall stability of the tailings stack. A pilot test was conducted, along with field and laboratory characterisation of the tailings. Both limit–equilibrium stability analyses and numerical analyses were carried out to verify the safety of the structure, which will be 70 m high, with an overall slope angle of 18° in its final configuration. The result of these geotechnical analyses is that the settlement will not affect the stability of the structure. This tailings disposal method entails lower risk and fewer space requirements compared to conventional methods. Even though this alternative represents a higher cost due to intensive handling of tailings, it has allowed the mining operation to maintain its regular schedule.